MppA, a Periplasmic Binding Protein Essential for Import of the Bacterial Cell Wall Peptide l-Alanyl-γ-d-Glutamyl-meso-Diaminopimelate - Park, James T. (American Society for Microbiology, 1998)
Mutants of a diaminopimelic acid (Dap)-requiring strain of Escherichia coli were isolated which failed to grow on media in which Dap was replaced by the cell wall murein tripeptide, l-alanyl-γ-d-glutamyl-meso-diaminopimelate. In one such mutant, which is oligopeptide permease (Opp) positive, we have identified a new gene product, designated MppA (murein peptide permease A), that is about 46% identical to OppA, the periplasmic binding protein for Opp. A plasmid carrying the wild-type mppA gene allows the mutant to grow on tripeptide. Two other mutants that failed to grow on tripeptide were resistant to triornithine toxicity, indicating a defect in the opp operon. An E. coli strain whose entire opp operon was deleted but which carried the mppA locus was unable to grow on murein tripeptide unless it was provided with oppBCDF genes in trans. Our data suggest a model whereby the periplasmic MppA binds the murein tripeptide, which is then transported into the cytoplasm via membrane-bound and cytoplasmic OppBCDF. In assessing the affinity of MppA for non-cell wall peptides, we have found that proline auxotrophy can be satisfied with the peptide Pro-Phe-Lys, which utilizes either MppA or OppA in conjunction with OppBCDF for its uptake. Thus, MppA, OppA, and perhaps the third OppA paralog revealed by the E. coli genome sequence may each bind a particular family of peptides but interact with common membrane-associated components for transport of their bound ligands into the cell. As to the physiological function of MppA, the possibility that it may be involved in signal transduction pathway(s) is discussed.